Exclusivity in Times of a Public Necessity: Balance of Interests in South Asia’s Compulsory Licensing Regime - Dhavalikar, Neha; Pandey, Ashok (Kathmandu School of Law Review, 2020)
The catastrophic impact of the COVID-19 pandemic on every facet of human life has made the requirement of a pharmaceutical breakthrough in the form of a vaccine more urgent than ever. The urgency has led to a hundred plus researches being underway, with tremendous amounts of capital and intellect invested. The vaccine being an invention, invites patent regulations and the rights of the patent holder associated with the invention. However, given the urgency of the situation, countries need to ensure hassle free access to the vaccine. Here, Compulsory Licensing regulations would play an important role. Beginning with a historical background of Compulsory Licensing under TRIPS, the authors analyse its subsequent amendment keeping in view the right of countries to give primacy to public health over intellectual property protection. The authors then highlight the diverse legislative positions of Compulsory Licensing in South Asia through the lens of the TRIPS position. The authors also comment upon Patent Pools, a comparatively new concept in the area of public health which is gaining spotlight. Further emphasis has been laid on keeping administrative impediments minimal with regards to the working of the intellectual property. This is important since firstly, the majority of the attempts underway are a collaborative innovation involving multiple stakeholders and secondly, multiple patent applications could be filed for different parts of a single invention leading to complexities while licensing. Finally, suggestions have been given as to how the patent regulations could be worked so as to maintain a balance between the rights of the patent holder and public health.